Computer vision syndrome and ergonomic practices among university office workers/ Elly Liyana Zainodin and Nor Aziyati Abu Bakar - Zainodin, Elly Liyana; Abu Bakar, Nor Aziyati (Faculty of Health Sciences, Universiti Teknologi MARA, 2019)
Introduction: Computer vision syndrome is prevalent among computer users, particularly office workers. Proper workstation design and good posture are essential preventive measures of computer vision syndrome among office workers to increase their work productivity and quality of life. A cross-sectional study was done to determine the symptoms of computer vision syndrome experienced by office workers in UiTM Selangor Puncak Alam Campus and their ergonomic practices and posture. Material and Methods: A self-administered questionnaire was distributed to 140 administrative staffs from 8 faculties. Results: The most common symptoms experienced by the office workers were shoulder pain (90%), followed by neck pain (88.6%), and headache (82.9%). Neck pain (p=0.004) and shoulder pain (p=0.027) was significantly related to using a laptop on the thigh. Headache was significantly associated with viewing computer screen at a distance lesser than 30 inches (p=0.038). Conclusion: High prevalence of CVS among the office workers is preventable by implementing strategies focusing on awareness of the visual ergonomics and adjustment to the workstation.